Metamorfoses da cidade medieval. A coexistência entre a comunidade judaica e a catedral de Viseu - Anísio Miguel de Sousa Saraiva (Medievalista)
Viseu’s status as political, ecclesiastical and commercial centre acted as a factor of development and attraction of merchants and Jews. The first testimonies of the Hebraic presence in this city are from the late 13th century, whose commune prospered mainly from the early 15th century, at the time when Viseu initiated a major process of rebuilt, after three decades of conflict and destruction which characterized the Ferdinand Reign and the first years of D. João I’s government.In this paper we will approach the multi confessional profile of medieval Viseu and the jewish contribution to the construction of its urban and social space, in the period prior to the hebraic expulsion, in 1496. We will analyze the outline of this coexistence and collaboration process, though not always peaceful, between jews and the cathedral. The latter, as owner of the vast majority of the urban property of the city, rolled as an important liaison between christians and the jewish minority and played a strong influence in their mechanisms of spatial organization. From certain issues analyzed in this extent, we will stand out the delocalization of the Jewish District mostly due to the consequences of the relations of power and of the defense of Jewish and Christian’s interests in the context of the reorganization of the 15th’s urban network of Viseu.